The Comparative Study of Profitability Ratios of Selected FMCG Companies in India - Joshi, Sanjana (Journal of Social Commerce, 2024)
This article is a comparative study of the profitability ratio of selected FMCG companies. The main purpose of this study is to analyze and compare profitability ratio of selected samples. This study is considered secondary data for the year from 2017-18 to 2021-22 and that collected by authentic websites. The sample selection is done by a non-probability sampling technique. Furthermore, the hypothesis are tested by one-way ANOVA. The result of hypotheses testing is that during the study period there is a significant difference between the selected ratio of selected FMCG companies. The findings of this study are that HUL, ITC and Britannia industries maintain good profit, but HUL pays a higher return on equity and is effectively utilize their capital, resources and assets compared to other companies. ITC and Britannia industries utilize the capital effectively and pay average return to their investors. The performance of Godrej consumer is very poor because they do not utilize their capital and not maintain their net profit as to why it can't provide more returns on investment. So, from an investers' point of view HUL companies are very beneficial for investment.